Optimization of Campus Teaching Programs to Improve Literacy and Numeracy Skills in SD Negeri 2 Pakisan - Ni Wayan Ayu Santi (International Journal of Educational Research Excellence (IJERE), 2023)
Each level of education has different characteristics of students, thus requiring additional efforts to improve literacy and numeracy. The purpose of this study is to find out the optimization of the campus teaching program to improve literacy and numeracy skills in SD Negeri 2 Pakisan. This research is a descriptive qualitative research. The methods used are interviews and observations. The results of this study are that there are several excellent work programs implemented by Campus Teaching Students Batch 5 including reading corners, reading aloud (reading fairy tales), teaching numeracy based on everyday life or fast counting numeracy (hicat), class bulletins, and establishing a guidance center integrated learning (bimberdu). The work program was effectively implemented for 16 weeks which illustrates the improvement in the ability of students at SD Negeri 2 Pakisan. The students' ability to understand the questions increased as evidenced by the results of the pre-test Minimum Competency Assessment (AKM) for literacy class of 36 percent and numeracy of 34 percent while the post-test results of AKM class increased to 75 percent for literacy and numeracy of 74 percent.